Turkey’s Hybrid Competitive Authoritarian Regime; A Genuine Product of Anatolia’s Middle Class - Stelgias, Nikolaos (The Levantine Review, 2016)
Few years since the 9/11 Attacks in New York and following its rise to power, the AKP has gradually established a so-called “competitive authoritarian regime,” in order to consolidate and secure its political power. This regime is hybrid and it is based on liberal principles (absence of tutelary authorities, protection of civil liberties, universal suffrage, free elections etc.). The AKP also provides for a reasonably fair level of political competition between the party in power (government) and the opposition. At the same time, however, the system shows some undemocratic features (violation of civil liberties, unfair elections, and uneven political competition.) This hybrid regime is based on three pillars: the state, the party and a newly emerged middle class in Anatolia. Through this hybrid regime Anatolia’s newly emerged middle class redefines its cultural and socio-economic relations.